ORGANIZATION OF CAREER GUIDANCE AT THE UNIVERSITY - Boris V. Zalivanskiy; Elena V. Samokhvalova (Высшее образование в России)
The article focuses on the problems concerning organization of career guidance at higher education institutions and presents an experience in organization of career guidanceat Belgorod National Research University. Basing on the survey conducted in 2012-2013, the authors reveal the typical shortcomings in arranging career guidance, such as the lack of strategic approach, predominance of enrolment measures over career counseling and career coaching, insufficient support of young people who deal with career-related challenges, inadequate reflexion of university administration. Besides strategic omissions, the authorsexplore the tactical mistakes such as vague addressee, inadequacy of methods, insufficientprocurement of resources. In a conclusion the authors formulate recommendation for raising the efficiency of career guidance measures.